Les effets antioxydants et antimicrobiens de l’extrait des graines de ricin récoltées dans la wilaya de Mostaganem - SNOUSSI, RIHAM SAIDA; KEBDANI, ABDELHAFID (My University, 2024)
The objective of this study of the antioxidant and antimicrobial effects of the extract from Ricinus Communis seeds harvested in the Mostaganem province. The antioxidant activity was assessed using the DPPH free radical, and the results indicate a crude extract yield of 7.5%. Furthermore, the extract is characterized by a significant total polyphenol content of 145.07 μg gallic acid equivalents/mg of extract, and a low flavonoid content of 71.81 μg quercetin equivalents/mg of extract. The study results confirm that the antioxidant activity of the R. communis seed extract is mainly attributed to phenolic compounds. The antimicrobial activity of the R. communis seed extract was tested against 6 microorganisms: Bacillus cereus ATCC 10876, Candida albicans ATCC 10231, Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 27853, and Staphylococcus aureus ATCC 33862 and Salmonella typhimurium ATCC 14028. The antagonistic activity results were expressed as the diameter of inhibition zones using the agar well diffusion test method, specifically towards Pseudomonas aeruginosa ATCC 27853, Staphylococcus aureus ATCC 33862, Bacillus cereus ATCC 10876, and Candida albicans ATCC 10231. No antimicrobial activity was observed against Escherichia coli ATCC 25922 and Salmonella typhimurium ATCC 14028. The R. communis seed extract shows a strong potential as an antioxidant agent due to its rich polyphenol composition, while its antimicrobial properties are more specific and effective against certain pathogens, which should be taken into consideration .
Keywords: Ricinus Communis; polyphenols; flavonoids; antioxydant activity; DPPH; antimicrobial activity; Pathogenic strains